Pengaruh Pemberian Air Rebusan Bawang Putih Terhadap Penurunan Kadar Koleterol di Puskesmas Sei Langka - Desy Rahmadani; Rizki Sari Utami Muchtar; Mira Agusthia (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Cholesterol is a fatty substance circulating in the blood, yellowish and waxy, which is produced by the liver and is needed by the body. Cholesterol is a group of lipids that are not hydrolyzed and is the main sterol in human body tissue. Hypercholesterolemia is a condition where the cholesterol level in the blood exceeds the normal limit, namely >200 mg/dl. The aim of this research was to determine the effect of boiled garlic water on reducing cholesterol levels in the elderly at the Sei Langkai Community Health Center. Pre-Experimental research method using One Group Pre-Post Test research design. Effectiveness is assessed by comparing the pre-test results with the post-test. The number of samples in this research was 15 respondents. The data testing method uses an observation sheet and a glucometer. The results of the research using the paired T-Test statistical test found a ρ value of 0.000 > 0.05. It can be concluded that there is an effect of giving boiled garlic water on reducing cholesterol levels in the elderly at the Sei Langkai Community Health Center in 2023. The recommendation from the research results is that boiled garlic water can be continued as an intervention to reduce cholesterol levels